Revelation of modernism responses to cultural crises in fin-de-siècle painting - Boime, Albert 1933-2008 (Univ. of Missouri Press, 2008)
"Examines the work of postimpressionist painters - Van Gogh, Seurat, Cézanne, and Gauguin - and how they responded to cultural and spiritual crisis in the avant-garde world. Boime reconsiders familiar masterpieces and draws analogies with literary sources and social, personal, and political strategies to produce revelations that have eluded most art historians"--Provided by publisher
Includes bibliographical references (p. 225-238) and index
Keywords: Geschichte 1800-1900; Painting, European / 19th century; Art and society / Europe / History / 19th century; Social problems in art; Geschichte; Art and society -- Europe -- History -- 19th century; Painting, European -- 19th century; Malerei; Nachimpressionismus; Kulturkrise; Europa